Circular stripe domains and cone state vortices in disk-shaped exchange coupled magnetic heterostructures. (3rd November 2022) - Zaiets, Oleksandr; Kravchuk, Volodymyr P; Pylypovskyi, Oleksandr V; Makarov, Denys; Sheka, Denis D
Abstract: Vertically stacked exchange coupled magnetic heterostructures of cylindrical geometry can host complex noncolinear magnetization patterns. By tuning the interlayer exchange coupling between a layer accommodating magnetic vortex state and an out-of-plane magnetized layer, one can efficiently realize new topological chiral textures such as cone state vortices and circular stripe domains. We study how the number of circular stripes can be controlled by both the interlayer exchange coupling and the sample geometrical parameters. By varying geometrical parameters, a continuous phase transition between the homogeneous state, cone state vortex, circular stripe domains, and the imprinted vortex takes place, which is analysed by full scale micromagnetic simulations. The analytical description provides an intuitive pictures of the magnetization textures in each of these phases. The possibility to realize switching between different states allows for engineering magnetic textures with possible applications in spintronic devices.